2020
DOI: 10.13057/biodiv/d210703
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence and specific genes of Salmonella sp. indigenous from Jember, Indonesia

Abstract: Abstract. Yulian R, Narulita E, Iqbal M, Rochmiyah D, Suryaningsih I, Ningrum DEAF. 2020. Detection of virulence and specific genes of Salmonella sp. indigenous from Jember, Indonesia. Biodiversitas 21: 2889-2892. The bacterium Salmonella sp. is the most common cause of foodborne infection in humans. It has the ability to invAde the host, Salmonellosis is highly influenced by the combination of chromosome and plasmid in which Salmonella Pathogenisitas Islands (SPIs) are the biggest gene in the chromosome that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…It makes the bacteriophage of this family have the ability to diffuse faster into the host cell compared to other groups. It is also related to the size of plaque produced on the surface of the medium, which is larger than for the other groups [15,[23][24][25]. Based on the plaque formed, it showed that the isolates obtained in this study were lysogenic, characterized by cloudy plaques [15].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…It makes the bacteriophage of this family have the ability to diffuse faster into the host cell compared to other groups. It is also related to the size of plaque produced on the surface of the medium, which is larger than for the other groups [15,[23][24][25]. Based on the plaque formed, it showed that the isolates obtained in this study were lysogenic, characterized by cloudy plaques [15].…”
Section: Discussionmentioning
confidence: 72%
“…Lysogenic bacteriophages produce cloudy plaques that can occur due to imperfect lysis of bacterial cells. The imperfections or imperfections that occur are related to the level of adsorption on weak host cells resulting in immature bacteriophage particles [ 3 , 24 , 25 , 28 , 29 ]. Lysogenic bacteriophages will form prophages that can reduce the productivity and growth of host bacteria [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding indicated that it is difficult to treat salmonellosis caused by MDR isolates because they have the ability to be pathogenic as evidenced by the presence of invA. This gene encodes membrane proteins in bacteria that are responsible for invading host intestinal cells [42,43]. In Salmonella isolates, invA was located in SPI-1, which plays an extremely important role in the invasion of host epithelial cells.…”
Section: Resultsmentioning
confidence: 99%